Thrasymachus' immoralism and pleonexia - Echeñique Sosa, Javier (Anales del Seminario de Historia de la Filosofía, 2022)
This article offers an interpretation of Thrasymachus’ Inmoralism, that is to say, of the set of judgements concerning the superior value of injustice in comparison with justice, issued by him in book I of Plato’s Republic (Resp. 336b-354c). It is argued that both the argument in support of these judgements and its implicit resource to the concept of πλεονεξία(personal advantage) cannot be interpreted descriptively, if they are to serve to justify the immoralists judgements. It is also argued that a particularly important subgroup of such judgements is supported by a peculiar conception of practical reason based on the concept of πλεονεξία. Finally, the comparison is made between this ‘pleonexic’ conception of practical rationality and the one that Plato advocates in the Republic.
Keywords: Thrasymachus; inmoralism; practical reason; injustice